Clinical Characteristics and Outcomes in Diabetic Patients with COVID-19 in Tripoli 2021 - Elktuni, Aida; Elshwekh, Halla; lita, Amna; mustafa, Ariej; Edaali, Omnia (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. The burden of the Severe Acute Respiratory Syndrome, Coronavirus-2 (SARS-CoV-2), which is also known as COVID-19 has been increasing worldwide, and causes many disabilities and deaths. Diabetes is a major risk factor contributing to the severity of illness and mortality from COVID-19. This study aimed to describe presenting, risk factors, and the clinical characteristics and outcomes of diabetic patients with Coronavirus Disease (COVID-19). Methods. A descriptive case series study was conducted in the Tajuora Rapid response team. Data was collected from patients with a history of diabetes, after taking verbal consent during May and June of 2021. A specific questionnaire was used to collect information including demographic data, diabetes status, comorbidities, clinical symptoms, blood tests, radiographical assessments, and outcomes of COVID-19. SPSS 21 package program was used for statistical analysis. Results. A total of 57 patients with confirmed COVID-19 presentations had diabetes. The majority of these patients are female, 31 (54.4%), and had a mean age (SD) of 64(±11.99) years and a mean duration of diabetes of 1(±6.83) year. Most patients in the study had Type 2 diabetes mellitus (DM), 44 (77.2%), with only 22.8% overall having Type 1 diabetes (n=13). 12.3% of patients displayed evidence of good glycemic control of their diabetes during the 4-12 weeks preceding sickness. 37 patients (64.9%) had other comorbidities including hypertension, ischemic heart disease, dyslipidemia, chronic renal failure, bronchial asthma, and rheumatoid arthritis. 41 patients (71.9%) are treated with insulin. During illness, all patients had a positive PCR result. Most patients, 64.6% (n=37), displayed a positive Chest HRCT scan. 38 patients (66.7%) had positive blood test results. 40 patients (70.2% of patients) were presented with more than three symptoms such as flue like symptoms, dyspnea, productive cough, diarrhea, and vomiting. First Laboratory data of the patients after diagnosis: (Mean ± SD) HBA1C 9.78(±9.93) %, white blood cell 9.38±3.72 (103/μL), lymphopenia 14.12(±10.38) %, D-dimer 3.09 (±9.032) μg/ml, Ferritin 580.31 (±815.75) mg/dl, CRP 81.82 (±92.26) mg/L, urea 42.02(±26.15) mg/dl. 71.9% (n=41) of patients received home management, and 34 (59.5%) needed oxygen therapy at home, 16 patients (28.1%) were transferred to the hospital for deterioration in their condition, and 10(17.5%) of them died due to complications of this diseases. The death rates from COVID-19 infection increase significantly with increasing age of diabetic patients, duration of diabetes- and more in the males. Conclusion. Diabetes is considered a comorbidity as diabetic patients that showed more than three COVID-19 symptoms had critical clinical outcomes such as ICU admission and death